Magnification and Refocusing Comparison in Cataract Surgery Using a Heads-Up Three-Dimensional Visualization System versus Conventional Binocular Microscopy - Ramírez Mejía M; Arroyo Muñoz L; Medina Perez AB; Mendoza Velasquez C; Ceja Martínez J; Camacho Ordonez A; Guerrero-Berger O (Clinical Ophthalmology, 2023)
Mariana Ramírez Mejía,1 Leticia Arroyo Muñoz,1 Ana Beatriz Medina Perez,1 Cristina Mendoza Velasquez,1 Jimena Ceja Martínez,1 Azyadeh Camacho Ordonez,1 Oscar Guerrero-Berger1,2 1Department of Anterior Segment Surgery, Fundación Hospital Nuestra Señora de la Luz, Mexico City, Mexico; 2Centro Oftalmológico Mira, Mexico City, MéxicoCorrespondence: Oscar Guerrero-Berger, Department of Anterior Segment Surgery, Fundación Hospital Nuestra Señora de la Luz, Ezequiel Montes 135, Tabacalera, Cuauhtémoc, Mexico City, 06030, Mexico, Tel +525551281140, Email droscarguerrero@gmail.comPurpose: To compare magnification and refocusing during phacoemulsification with the NGENUITY® 3-D Visualization System (3-D) versus the conventional microscope (CM) OPMI LUMERA 700.Setting: This study was performed in the Department of Anterior Segment of the Fundación Hospital Nuestra Señora de la Luz.Design: Prospective, randomized, cross-sectional, multi-surgeon, and comparative study.Methods: This study enrolled 100 patients (eyes) scheduled for phacoemulsification to measure the number of times changes in focusing and magnification were needed during cataract surgery.Results: Our study included 100 patients. From the endpoints evaluated, “zoom-in” showed statistically significant differences for all of the four predefined cataract surgery steps (means: Step 1, 0.38 (CM) vs 0.08 (3-D); Step 2, 0.36 (CM) vs 0.06 (3-D); Step 3, 0.54 (CM) vs 0.22 (3-D); Step 4, 0.56 (CM) vs 0.24 (3-D); all comparisons, p < 0.05). In Step 4, there was a statistically significant increased use of “focus-out” for the 3-D system (mean 0.16 (CM) vs 0.58 (3-D); p < 0.05). “Focus-in” and “zoom-out” showed no group differences for all steps. The duration of surgery with the 3-D system was longer at each step and overall. The percentage of light intensity did not show a statistically significant difference between both systems, with a mean of 99.45 for CM vs 98.43% for the heads-up system.Conclusion: The heads-up 3-D system is a safe option that offers excellent magnification for anterior segment visualization. The surgical time is longer, but adjusting settings like light intensity and brightness may facilitate some surgical steps early in the learning curve.Keywords: three-dimensional visualization, cataract surgery, heads-up surgery, visualization systems